Nanodiamond as a drug delivery system: Applications and prospective - Khalid Mohamed El-Say (Journal of Applied Pharmaceutical Science)
With the rapid development of nanoscience and nanotechnology, a wide variety of nanomaterials have been synthesized and discovered. Revolutionary particles called nanodiamonds (NDs) have been considered for use in several medical applications due to its unique mechanical, chemical, optical, and biological properties. It has also sensing, imaging, and drug delivery properties. The study associated with the interface between ND and life sciences which is important for development of effective drug delivery systems.
Keywords: Nanotechnology, nanomaterial, nanodiamond, drug delivery system.